Are Sc—C and Sc—P Bonds Reactive in Scandium Phosphinoalkylidene Complex? Insights on a Versatile Reactivity1. Issue 10 (27th July 2018) - Mao, Weiqing; Xiang, Li; Lamsfus, Carlos Alvarez; Maron, Laurent; Leng, Xuebing; Chen, Yaofeng
Abstract : The peculiar electronic structure of scandium phosphinoalkylidene complex [LScC(SiMe3 )PPh2 THF] (L=[MeC(NDIPP)CHC(NDIPP)Me] − ), DIPP=2, 6‐( i Pr)2 C6 H3 ) leads to an interesting versatile reactivity, which is demonstrated both experimentally and computationally. Abstract: The peculiar electronic structure of scandium phosphinoalkylidene complex [LScC(SiMe3 )PPh2 THF] (L=[MeC(NDIPP)CHC(NDIPP)Me] − ), DIPP=2, 6‐( i Pr)2 C6 H3 ) leads to an interesting versatile reactivity, which is demonstrated both experimentally and computationally. The complex undergoes [2+2] cycloaddition reactions with alkynes, and easily activates various X—O bonds such as C—O of propylene oxide, N—O of 3, 5‐dimethylisoxazole, B—O of pinacolborane and Si—O of triethoxysilane. These reactions occur on the Sc—C bond of the phosphinoalkylidene complex. Interestingly, the Sc—P bond can also be activated as the presence of a Sc—C—P three center π interaction in the complex allows performing C—F activation of 2, 6‐difluoropyridine and 1, 2 addition with imine or ketone. The complex also reacts with metal complexes, [(COD)RhCl]2 and (Ph3 P)AuCl, to form structural intriguing heterobimetallic complexes.